Economic and Monetary Integration and the Aggregate Demand for Money in the EMS. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1990)
This study shows that the aggregate demand for M1 in the group of countries participating in the Exchange Rate Mechanism (ERM) of the European Monetary System can be expressed as a stable function of ERM-wide income, inflation, interest rates, and the exchange rate of the European Currency Unit (ECU) vis-a-vis the U.S. dollar. A notable feature of the model is the rapid elimination of monetary disequilibria, in contrast with most single-country estimates which tend to find implausibly slow adjustment. These results are suggestive: if robust, they would indicate that, even at the present stage of economic and monetary integration, a European central bank could, in principle, implement monetary control more effectively than the individual national central banks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet